An Educational Curriculum and its Effect on Improving the Values of Some Kinematic Variables and the Accuracy of the Smash Skill during the Feather Hitting Stage - Mohammed Ismael, Maher; Salman Abbas Al-Rubaye, Ali; Youssuf Abdulzahra, Yaqub (International Journal of Psychosocial Rehabilitation, 2020)
Research Objectives: Preparing a curriculum for the Spiking Skill. Identify the impact of the educational curriculum on the values of some kinematic variables and the accuracy of the crushing blow skill during the hitting stage with the badminton. Research community: The players of the Maysan Governorate national team were represented by the badminton for the category of applicants. The research sample and the method of its selection were the research community, which was (8) players, while the research sample was (6) players; two players were excluded for conducting the exploratory experiment, and the percentage was (75%) from the original community, and the researcher made homogeneity on some research variables (length, weight, age, and arm length) of the subjects. The scientific method - the researcher used the experimental one-group approach to suit the solution of the research problem. Statistical treatments: arithmetic mean, standard deviation, t-law for correlated samples, and coefficient of variation. Conclusions: the educational curriculum has an effective role in improving the accuracy of the smash skill, and the proposed exercises have a positive effect in improving the values of the kinematic variables in the research. Recommendations: conducting other studies and research on different groups and different skills and for all sexes. The methods of learning must be in line with the needs and capabilities of the players.